From Productivity Strategy to Business Case: Choosing a Cost-Effective Intervention for Workplace Innovations - Oeij, Peter; de Looze, Michiel; ten Have, Klaas; van Rhijn, Gu; de Graaf, Bart (Pontificia Universidad Católica del Perú. CENTRUM, 2012)
The article presents an approach to developing cost-effective interventions for workplace innovations for entrepreneurs who seek to enhance the productivity of an organization. The business case method is used to extend the Q4-model of productivity, which supports developing a productivity strategy in order to choose a cost-effective intervention. The approach offers the opportunity to trade off quantitative factors against qualitative factors; therefore, it is applicable to both profit sectors of industry and nonprofit sectors. The study sets out the steps in the approach and presents two case studies from different industrial sectors (public services and manufacturing) in which the approach has proved applicable. The Q4-model provides practical support to entrepreneurs in their efforts to innovate and improve productivity and is not for measuring the quantity and quality of input and output factors. Entrepreneurs are supported in developing a productivity strategy, combining a mix of quantity and quality input and output factors, and in the transformation of this strategy into a practical intervention. To facilitate the entrepreneurs to choose from different commercial options, the Q4-approach allows for the definition of its business case.
Keywords: Q4-model of productivity; Business case; Intervention; workplace innovation; https://purl.org/pe-repo/ocde/ford#5.02.04